Modeling of Compound Gaussian Sea Clutter Based on Inverse Gaussian Distribution - Yan Liang; Sun Pei-lin; Yi Lei; Han Ning; Tang Jun (Leida xuebao, 2013)
The Compound-Gaussian (CG) distribution is widely used for modeling the non-Gaussian clutter, and its texture component describes the non-Gaussian properties of clutter. In this paper, a CG model with an inverse Gaussian texture distribution is proposed, called Inverse Gaussian Compound Gaussian (IG-CG) distribution, and its distributional properties are derived. The IPIX radar lake-clutter measurements are analyzed, and the results show that the two-parameter IG-CG distribution model fits the real radar data better than single parameter IG-CG distribution model and K distribution model.